2007
DOI: 10.1002/jctb.1776
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of lipase production by Penicillium simplicissimum in soybean meal

Abstract: BACKGROUND: Lipase production by Penicillium simplicissimum using soybean meal as substrate has been investigated. A factorial design technique was used to evaluate the effects of incubation temperature, initial moisture of the meal and substrate supplementation with low cost supplements, on lipase production. Soybean oil and wastewater from a slaughterhouse, which is rich on oil and fat, corn steep liquor and yeast hydrolysate, were tested as supplementary carbon and nitrogen sources.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0
3

Year Published

2008
2008
2017
2017

Publication Types

Select...
8
1
1

Relationship

5
5

Authors

Journals

citations
Cited by 57 publications
(45 citation statements)
references
References 27 publications
2
36
0
3
Order By: Relevance
“…Sekhon et al,(2006) has reported on the use of malt extract as a source of nitrogen for lipase production. There exist reports on the use of soy meal as a source of nitrogen but more reported that it was found not to be the best source with any organism (Essakkiraj et al, 2010;Vargas et al, 2008;Kempka et al, 2008). This could mean that soymeal contain certain cations which repress or inhibit lipase activity and can only be employed when these cations had been removed by an ionexchanger; which when considered from the economic standpoint may not be ideal or good for lipase production or may be costintensive.…”
Section: Resultsmentioning
confidence: 99%
“…Sekhon et al,(2006) has reported on the use of malt extract as a source of nitrogen for lipase production. There exist reports on the use of soy meal as a source of nitrogen but more reported that it was found not to be the best source with any organism (Essakkiraj et al, 2010;Vargas et al, 2008;Kempka et al, 2008). This could mean that soymeal contain certain cations which repress or inhibit lipase activity and can only be employed when these cations had been removed by an ionexchanger; which when considered from the economic standpoint may not be ideal or good for lipase production or may be costintensive.…”
Section: Resultsmentioning
confidence: 99%
“…SSF with agriculture and food residues is well suited for enzyme production (30). the effect of three factors on the lipase production rate was investigated, namely: type of mixed substrate, initial pH (6.0 and 7.0), and time of fermentation (72 h, 96 h and 120 h).…”
Section: Resultsmentioning
confidence: 99%
“…The enzyme was immobilized on a carrier textile cloth by using co-fixing agents (polyethylene glycerol, tween and span, gelatine and lecithin). Vargas et al (2008) studied the lipase production by Penicillium simplicissimum isolated from the babassu oil industry by using soybean meal as substrate. The enzyme activity was 30U.g 1 dry substrate in the reaction with an olive oil emulsion.…”
Section: New Sources Of Lipasesmentioning
confidence: 99%